ANALISIS DESKRIPTIF KITAB SHAHIH AL-BUKHARI - Hamzah Muchtar, Evan (JIQTA: Jurnal Ilmu Al-Qur'an dan Tafsir, 2022)
This article discusses the Book of Sahih al-Bukhari which includes writing about the Biography of Imam al-Bukhari, the full name of the book of hadith, the number of traditions, the assessment of scholars on the Book of Sahih al-Bukhari, the Book of Sahih al-Bukhari and the systematics of discussion in the Book of Sahih al-Bukhari. This study uses qualitative research methods with the type of literature review research. Based on the results of the study, it can be concluded that the book of Sahih al-Bukhari is the first book of hadith that contains only authentic traditions. Sahih al-Bukhari is the most authentic book after the Qur'an. Through his work, al-Bukhari earned the title of Amirul Mu'minin in the field of hadith.